2023
DOI: 10.3389/fmicb.2023.1043430
|View full text |Cite
|
Sign up to set email alerts
|

Three new yeast species from flowers of Camellia sinensis var. assamica collected in Northern Thailand and their tannin tolerance characterization

Abstract: Our recent research study focused on Miang fermentation revealed that tannin-tolerant yeasts and bacteria play vital roles in the Miang production process. A high proportion of yeast species are associated with plants, insects, or both, and nectar is one of the unexplored sources of yeast biodiversity. Therefore, this study aimed to isolate and identify yeasts of tea flowers of Camellia sinensis var. assamica and to investigate their tannin tolerance, which is a property essential to Miang production processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
2
5
0
Order By: Relevance
“…( Camellia) sinensis var. assamica , as has been indicated in previous studies [ 17 , 18 ]. They were stored at −20 °C in yeast extract-malt extract broth (YMB) supplemented with 15% (v/v) glycerol.…”
Section: Methodssupporting
confidence: 78%
See 2 more Smart Citations
“…( Camellia) sinensis var. assamica , as has been indicated in previous studies [ 17 , 18 ]. They were stored at −20 °C in yeast extract-malt extract broth (YMB) supplemented with 15% (v/v) glycerol.…”
Section: Methodssupporting
confidence: 78%
“…All yeast species were isolated from Miang, the fermented tea leaves of northern ethnic people of Thailand, and the flowers of Assam tea collected near the Miang plantation areas. Current research has found that the diversity of the yeast species of Miang were associated with the yeast communities present in the flowers of the Assam tea [ 17 , 18 ]. Nectar consists of sucrose as the main sugar, followed by glucose and fructose, which are varied depending upon the flower type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Species within the Wickerhamiella clade have been documented in various ecological niches, with a predominant association with flowers, nectar, and floricolous insects [1,7,[29][30][31][32]. Numerous species of the genus Wickerhamiella, such as W. australiensis, W. occidentalis, W. drosophilae, W. lipophila, W. alocasiicola, W. musiphila, W. jalapaonensis, W. azyma, W. pagnoccae, W. kiyanii, W. fructicola, W. kurtzmanii, W. nakhonpathomensis, W. bidentis, and W. camelliae, have been isolated from flowers [6,7,33,34]. Similarly, W. lachancei sp.…”
Section: Resultsmentioning
confidence: 99%
“…Nectar yeasts often exhibit nutritional specialization and can be also found in flowers, floricolous insects, fruits, and plant leaves [2]. The exploration of yeast diversity from flowers and their interacting insect visitors has led to the discovery of over 50 new yeast species in the past decade, predominantly belonging to genera such as Metschnikowia, Wickerhamiella, Starmerella, and Kodamaea [1,[3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%